AKTIVITAS ANTIOKSIDAN TUMBUHAN GENUS MANGIFERA DENGAN METODE DPPH (1,1-diphenyl-2-picrylhydrazyl) : MINI REVIEW - Jannah, Nurul; Hairani, Rita; Marliana, Eva (JURNAL ATOMIK, 2024)
Mangifera is a genus of the Anacardiaceae family of mangoes spread across Sumatra, Kalimantan, Java, and Bali. Several species of the genus Mangifera have been extensively researched on phytochemistry and antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The study explains that several species of the genus Mangifera contain secondary metabolite compounds, such as flavonoids, phenolics, tannins, saponins, alkaloids, triterpenoids, and quinones. The results of several studies explain that the Mangifera genus has antioxidant activity with an inhibitory concentration (IC50) value generally <50 ppm, which is a strong category, so it has the potential to be an antioxidant. Keywords : Mangifera, phytochemical screening, antioxidant activity